Application of STATCOM to improve the LVRT capability of DFIG during VSC fire-through - Abdou, A.; Abu-Siada, Ahmed; Pota, H. (Elixir International Journal, 2013)
Due to the convincing revolution in power electronic technology and the growing concern about greenhouse effect that is intensified due to the burning of fossil fuels, wind power generation is significantly increasing globally. Transmission line operators developed various grid codes that require wind turbines to remain connected to support power grids during intermittent disturbance events which motivated researchers to investigate the impact of various grid disturbances on the overall performance of the wind energy conversion system (WECS). No attention, however, has been given to investigate the impact of voltage source converter (VSC) faults on the low voltage ride through (LVRT) of the DFIG-based WECS. In this paper, the impact of a fire-through fault when it takes place within the RSC and the GSC on the LVRT capability of the DFIG are investigated. A STATCOM controller to mitigate the effects of these faults is proposed. The DFIG compliance with recently released LVRT grid codes under the studied faults with and without the STATCOM were examined and compared. Simulation results indicated that fire-through faults have a serious impact on the DFIG voltage profile, especially when they occur in the GSC. The proposed STATCOM controller is effective in improving the dynamic performance of the DFIG during the studied faults and hence the connection of wind turbine to the grid can be maintained.